Overview of Self-Regulated Learning among Nursing Students - Yosep, Iyus; Mardhiyah, Ai; Maulana, Indra; Hernawaty, Taty (Jurnal Pendidikan Keperawatan Indonesia, 2024)
Introduction: Many students experience academic stress during their learning process, which can negatively impact their academic performance. One effective way to manage this stress is by improving self-regulated learning (SRL). Students with high levels of SRL are better equipped to manage their learning, leading to improved academic achievement. Objective: This study aims to describe the levels of self-regulated learning among nursing students. Methods: A quantitative descriptive design was used in this study. The sample was selected using a convenience sampling technique, and data were collected using the Self-Regulated in Online Learning Questionnaire (SOL-Q). The data were analyzed using univariate descriptive analysis and presented in tables. The sample consisted of 210 nursing students. Results: The demographic characteristics of the participants showed that the majority were female (54.1%) and aged between 17-19 years (57.4%). The findings revealed that 60% (126 students) demonstrated low self-regulation in their learning, suggesting that many students face challenges in managing their academic responsibilities. Efforts to overcome these problems require collaboration between institutions and health workers to improve Self-regulated learning for nursing students. Conclusion: Self-regulated learning is important to improve the effective learning process in students.